In-Service Teachers’ Perception on the Use of English Children’S Song to Enhance Vocabulary for Early Childhood - Bate’e, Marlinda; Hertiki, Hertiki (Journal of English for Academic and Specific Purposes (JEASP), 2024)
This research purposes at exploring In-Service Teacher’s Perception on the use of English Children’s Song to Enhance Vocabulary for Early Childhood. This study uses qualitative method with descriptive approach. The data in this study are observation, interview and documentation. The source data came from two teachers in different school, SDN K and SDN S already be interviewed. The data were analyzed by using thematic. This study conveys three things result from two teachers’ perception. The first, the characteristic of the song in English learning process for children. Perception of two teachers almost have same perception of characteristic of the song. To teach songs to children, songs must be adapted to the age of the child, songs that are happy, the words or sentences are not too long, and songs that contain children's lives. The second, English song can enhance vocabulary for children. Through the songs, children are easier to memorize and understand vocabulary, and it helps students to pronounce correctly. The third, English song can memorize vocabulary easily. Translating Indonesian children's songs into English can be a valuable instrument for improving vocabulary in a fun and engaging way.